Controlled Blood Pressure Rise Through Limited Fluid Resuscitation in Treating Multiple Injuries in Permutation with Shock and its Impact on Post-Resuscitation Hemoglobin Level - Muhammad Mohsin Riaz, Muhammad Arslan Zahid, Mahum Tanveer, Omer Farooq, Muhammad Nouman Sheikh, Tania Naveel, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Trauma is the largest root of death because 30% of trauma-related casualties are attributable to hemorrhages. Concerns were heaved about aptness of traditional doctrine of vigorous crystalloid resuscitation in these cases. Objectives: The study comparatively studied conventional and limited fluid resuscitation in control of blood pressure elevation and their effects on hemoglobin concentration. Methods: This exploratory study was conducted in Ali Fatima Hospital/ Abu Umara Medical and Dental College, Raiwind Road Lahore, comprising 340 patients who presented to the Trauma Center, with intensified multiple organ injury or shock and then transferred to ICU. Patients were allocated into two groups viz experimental (n=170) and control (n=170) and were administered with intravenous fluids via conventional mode and experimentally through limited resuscitation. Results: Recovery time of the experimental group (2.78+1.41) was significantly lesser (p<0.05) than control (3.41+1.78). Hemoglobin concentration was significantly improved (p<0.05) in the patients of experimental groups (mean 11.12+2.39 g/dl), then control. The incidence of mortality, shock, hypothermia and hemorrhages was significantly reduced (p<0.05) in experimental group, while hypoxia and intravascular coagulation were increased (p>0.05) in patients of the control groups. Practical implications: The clinicians should shift to limited fluid resuscitation to minimize the complications in trauma patients. Conclusion: The recovery rate and effective hemoglobin concentration were significantly improved in experimental patients, with reduced incidence of complications due to hemorrhages. Keywords: Electrolytes; Hypothermia; Hypoxia; Multiple organ failure; Resuscitation